Proposal of new genera and species of the subfamily Diosaccinae (Copepoda: Harpacticoida: Miraciidae) - Gómez, Samuel; Corgosinho, Paulo Henrique Costa; Rivera-Sánchez, Karen I. (European Journal of Taxonomy, 2021)
Representatives of several genera of the family Miraciidae (Copepoda: Harpacticoida) were found in sediment samples taken in the year 2019 from a coastal system in north-western Mexico. The subfamily Diosaccinae (Miraciidae) was by far the most diverse taxon followed by the subfamily Stenheliinae (Miraciidae). Here we report on a new miraciid species, Typhlamphiascus medici sp. nov., and provide a new amended diagnosis for Typhlamphiascus Lang, 1944 along with a key to its species. Additionally, Typhlamphiascus lamellifer lamellifer (Sars, 1911) and T. l. capensis Kunz, 1975 are considered as distinct species and the latter is given full species rank. Upon preliminary inspection, another diosaccin species was thought to be a derived form of Bulbamphiascus Lang, 1944. This promoted us to perform a more in-depth phylogenetic analysis. Our results showed that the new presumed derived form of Bulbamphiascus represents a new genus, Spinodiosaccus gen. nov. and that the genus Bulbamphiascus, which we propose a new amended diagnosis for, could be split into different genera. Also, the possible relationships amongst the different diosaccin clades found during our analyses are commented. We give a brief ecological analysis on the distribution of T. medici sp. nov. and S. primus gen. et sp. nov. in the Urías system.